ERROR ANALYSIS ON THE USE OF CONDITIONAL SENTENCE TYPE 1 FOUND IN DAILY ASSESSMENT AT ELEVENTH-GRADE OF SMA N 1 BAE KUDUS ACADEMIC YEAR 2022/2023 - Prahardika, Novia Sindi; Utomo, Slamet; Nurcahyo, Agung Dwi (Universitas Muria Kudus, 2023)
An analysis is very important to know the students’ errors. Then the teacher can pay attention to the students’ errors. Therefore, the objectives of this research is to identify the error types which did by the eleventh-grade of SMA N 1 BAE KUDUS Academic Year 2022/2023 made in constructing conditional sentence type 1. The research employed the content analysis qualitative research. The subject of the research was the students of XI IPS 2 at SMAN 1 Bae Kudus Academic Year 2022/2023, while the sample were 36 students. In data collecting technique, the researcher used student daily assessment given by the English teacher. Then, the researcher analysed and classified the students error based on Surface Strategy Taxonomy by Dulay’s theory. They are omission, addition, missformation, and missorder. After analysing the data, the researcher found 166 incorrect items which made by the students in making conditional sentence type 1. The proportions (frequency and percentage) of the students error are omission 43 items or 25,9%, addition 74 items or 44,5%, missformation 39 items or 23,4%, and missorder 10 items or 6,2%. Therefore, the result from this research show that addition is the highest error was made by the students.Furthermore, we can conclude that the highest frequency types of error made by the students of XI IPS 2 at SMAN 1 Bae Kudus Academic Year 2022/2023 in writing conditional sentence type 1 found in their daily assessment is addition with the percentage 44,5% items of error.